1994
DOI: 10.1007/bf01277622
|View full text |Cite
|
Sign up to set email alerts
|

New investigations on acute toxicities of vanadium oxides

Abstract: The "in-vivo'-toxicity of the Vanadium-oxides V20 5 and V203 (administered orally, dermally and by inhalation) has been reinvestigated with particular emphasis on the safety and handleability of vanadium-oxides in the vanadium processing industry. Chemical-thermodynamic properties of vanadium-oxides make it likely that some earlier results on vanadium-toxicities have introduced artefacts as a consequence of the administration-techniques used. Special precautions have therefore been taken to avoid any chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1
3

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 11 publications
0
11
1
3
Order By: Relevance
“…Nach wiederholter Inhalation zeigt Divanadiumpentaoxid eine Tendenz zur Akkumulation in der Lunge. Nach oraler Gabe werden 2,6 -3% resorbiert (ATSDR 1992;HSE 2003;IARC 2005;NTP 2002;WHO 2001 (Leuschner et al 1994). In einer anderen Studie wurde bei Exponierten, die einen Vanadiumspiegel von 7,73 ± 7,86 mg/l Serum (nicht Exponierte 3,43 ± 3,18 mg/l) aufwiesen, eine Vanadiumausscheidung von 14,57 ± 13,31 mg/g Kreatinin (nicht Exponierte 1,13 ± 0,26 mg/g Kreatinin) beschrieben (Ivancsits et al 2002).…”
Section: Aufnahmeunclassified
See 2 more Smart Citations
“…Nach wiederholter Inhalation zeigt Divanadiumpentaoxid eine Tendenz zur Akkumulation in der Lunge. Nach oraler Gabe werden 2,6 -3% resorbiert (ATSDR 1992;HSE 2003;IARC 2005;NTP 2002;WHO 2001 (Leuschner et al 1994). In einer anderen Studie wurde bei Exponierten, die einen Vanadiumspiegel von 7,73 ± 7,86 mg/l Serum (nicht Exponierte 3,43 ± 3,18 mg/l) aufwiesen, eine Vanadiumausscheidung von 14,57 ± 13,31 mg/g Kreatinin (nicht Exponierte 1,13 ± 0,26 mg/g Kreatinin) beschrieben (Ivancsits et al 2002).…”
Section: Aufnahmeunclassified
“…Die Lunge war blutig, ödematös, entzündet und wies vaskuläre Stauungen auf (Leuschner et al 1994 Leuschner et al 1994).…”
Section: Inhalative Aufnahmeunclassified
See 1 more Smart Citation
“…Vanadium oxides vary in their toxicity, with vanadium pentoxide (V 2 05) more toxic than vanadium trioxide (V 2 0 3 ) (Leuschner et al 1994 Lithium cells and batteries may be transported under this entry if they meet the fo llowing requirements:…”
Section: Aluminummentioning
confidence: 99%
“…However, particularly in the case of Cr, the oxidation state is crucial, since Cr(III) is considered to be an essential trace element for the human metabolism, whereas Cr(VI) is carcinogenic [11,12]. In the case of V, the oxidation state also has to be considered because the toxicity of V increases with increasing valency [13][14][15]. For basic oxygen furnace (BOF) slags, Chaurand et al [16,17] showed that in powder samples, Cr is present as Cr(III) prior to and after water leaching and that V is predominately present as V(IV) and increases its oxidation state to V(V) during ageing.…”
Section: Introductionmentioning
confidence: 99%